Qualitative enquiry on factors affecting antibiotic prescribing at primary healthcare facilities in Addis Ababa, Ethiopia - Altaye, Fikru Worku; Thupayagale-Tshweneagae, Gloria; Mfidi, Faniswa Honest (Frontiers in Medicine, 2024)
Background. The major driver of antibiotic resistance is the huge increase in antibiotic prescribing, especially in low-and middle-income countries. Aim. The aim of this study was to explore factors affecting antibiotic prescribing at primary healthcare facilities in Addis Ababa, Ethiopia. Methods. The study was part of a three-phased explanatory sequential mixed method design. The study was conducted in five primary healthcare facilities through in-depth interview of 20 prescribers and 22 key informants using pre-prepared interview guides. The data was analysed through thematic content analysis by applying ATLAS.ti 9 software. Results.The antibiotic prescribing decision of prescribers was shown to be affected by various factors.The factors related with prescribers include not updating oneself on antibiotic use and antibiotic resistance, not reviewing patient history, not considering the issue of antibiotic resistance during prescribing and competency problem. The patient-related factors were low awareness about antibiotics, lack of respect to prescribers and pressure on prescribers. Shortage of antibiotics and laboratory reagents, lack of updated antimicrobial resistance information, patient load, inadequate capacity, private sector practice, inadequate follow-up and support, and health insurance membership were the system-related factors. Appropriate interventions should be designed and implemented to address the identified factors and improve the prescribing practice.